General practice wide adaptations to support patients affected by DVA during the COVID-19 pandemic: a rapid qualitative study - Dixon, S; De Simoni, A; Szilassy, E; Emsley, E; Wileman, V; Feder, G; Downes, L; Barbosa, EC; Panovska-Griffiths, J; Griffiths, C; Dowrick, A (BioMed Central, 2023)
Background Reporting of domestic violence and abuse (DVA) increased globally during the pandemic. General Practice has a central role in identifying and supporting those affected by DVA. Pandemic associated changes in UK primary care included remote initial contacts with primary care and predominantly remote consulting. This paper explores general practice’s adaptation to DVA care during the COVID-19 pandemic.